Peculiarities of differential diagnosis of malignant and benign ovarian tumors in girls (case report of immature teratoma of the ovary) - Elena V. Sibirskaya; Irina V. Karachentsova; Ivan N. Skapenkov; Andrey A. Naumenko; Ivan I. Petinov; Polina O. Nikiforova (Педиатрическая фармакология)
Germ  cell tumors  are  a heterogeneous group  of tumors  differentiating from  primary germ  cells of  embryonic gonads and  their derivatives. This case  report demonstrates the diagnostic algorithm and diagnostic tactics of a rarely encountered histological type of ovarian germ cell tumor.